Influence of Synthetic and Natural Fibers on the Characteristics of Wood-Textile Composites - Cosereanu, Camelia; Curtu, I; Lunguleasa, A; Lica, D; Porojan, M; Brenci, LM; Cismaru, I; Iacob, I (My University, 2009)
The paper presents the results of the research work on the evaluation of the mechanical properties (bending strength, MOE, shearing strength of the adhesive bond) of the laminated wood-textiles composite materials made of wood veneer (beech and poplar wood) and textiles: natural fabric made of jute (sackcloth) and woven fabric with synthetic fiber insertions (MTR-polyester, cotton, staple rayon). The layers of veneer and textiles were glued together by two types of adhesives, successively: a natural one (bone glue) and a polyvinyl adhesive (Jowacoll 107.10). Four types of wood-textile composite samples have resulted, as follows: beech veneer - sackcloth glued with bone glue, beech veneer - sackcloth glued with polyvinyl adhesive, poplar veneer- sackcloth glued with bone glue and beech veneer- woven fabric with MTR glued with bone glue. The samples resulted were loaded to the bending strain and the bending strength and MOE were calculated with the value of breaking force obtained for each tested sample. The shearing strength of adhesive bond has been also experimentally determined in order to,establish which adhesive is more appropriate to be used both with wood and textile materials into the composites. The influence of the flexibility of the synthetic fibers on the elastic properties of the resulted composites has been also investigated by determining MOE of the corresponding composites. Based on the results obtained, it is concluded that the synthetic fibers (67%) contained by woven fabric with MTR does not increase MOE of the composites, whilst the natural jute fabric behaviour into the wood-textile composites gives unexpected results in strength and elasticity of the new product.
Keywords: synthetic fibers; MOE; bending strength; shearing strength; composite; elasticity